(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The article considers the conceptual foundations of the regulators of the institution in the conditions of innovative development of the economy. It notes that the institution as a process of defining and securing norms, rules, statuses, roles is regulated and modeled. On the basis of system analysis, a classification is given which, in the author’s opinion, is applicable to research and analysis of the internal structure of the system mechanism with the aim to identify effective forms and instruments of state regulation of insurance activities.